Microbiologic spectrum and susceptibility of isolates in delayed post-cataract surgery endophthalmitis - Jindal, Animesh (Clin Ophthalmol, 2015)
The objective of this study was to evaluate the microbiological spectrum and antimicrobial susceptibility of isolates in delayed post-cataract surgery endophthalmitis. A retrospective review of 33 consecutive patients with culture proven delayed post-cataract surgery endophthalmitis was done from January 2006 to March 2013. There were 22 bacterial and eleven fungal cases. Common isolates were Streptococci (seven cases), coagulase-negative staphylococci (five), Gram-negative bacilli (seven), Nocardia (two), Aspergillus (five), Candida (five). Gram-positive cocci were most susceptible to vancomycin and gatifloxacin (91.7%). Gram-negative isolates were most susceptible to ofloxacin (85.7%). Fungi being slow growing organisms are an important cause of delayed post-cataract surgery endophthalmitis.